Evaluation of the allelopathic potential of oat genotypes at the initial period of cycle - Jacobi, Ubiratã Soares (2000)
Oats (Avena spp.) represent one of the most important crops in the South of Brazil during the winter growing season. In its plants there are allelopathic substances present, which refer the importance of the understanding of this phenomenon in the crop. The aim of this work was to estimate the allelopathic potential of different genotypes based on the analyses of their initial phase as well as on the evaluation of their allelochemicals. Results of this study showed that oat genotypes present allelopathic potential. Genotypes that present greater allelopathic effects during the initial period are UPF 13, UFRGS 9, UFRGS 10, and UFRGS 6. In the same way, those genotypes that exhibit lesser effects are UFRGS 12, UFRGS 17, UFRGS 884077, and UPF 12. The effects caused by the allelochemical scopoletin are similar to those observed by oat genotypes, suggesting a cause and effect relationship.